Impact of Constructivist Teaching Methods of Teaching Mathematics on Students’ Achievement - Tiwari, Dharma Datta (Shaheed Smriti Journal, 2024)
This study aims to evaluate the effectiveness of constructivist teaching methods in secondary mathematics education in Nepal, with a focus on their impact on student achievement. The research examines the extent of constructivist teaching practices in Nepalese classrooms and their relationship with student performance. Data was collected through structured classroom observations, ensuring validity and reliability. The study reveals that while constructivist methods showed a positive correlation with student achievement, the implementation remains limited due to systemic constraints, such as curriculum rigidity and teacher training challenges. Comparative analysis across districts indicated no statistically significant differences between constructivist and traditional teaching approaches, suggesting the persistence of traditional teaching norms. The study found a moderate positive correlation between constructivist teaching practices and student academic performance, highlighting the potential benefits of student-centered learning methods. The findings emphasize the need for further research and educational reforms to fully integrate constructivist approaches in Nepal's mathematics classrooms.